The role of forage legume fallows in supplying improved feed and recycling nitrogen in subhumid Nigeria - Tarawali, G.; Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1995)
Sub-Saharan Africa is experiencing substantial land degradaton and declining soil fertility. This has led to decreasing total agricultural productivity. Introducing forage legume rotations into crop-livestock systems can stabilise agricultural productivity. In addition to providing high-quality forage for animals, legumes can improve soil characteristics for crop production. Research conducted to test the impact of forage legumes on livestock productivity in the subhumid zone of Nigeria showed that cattle grazing Stylosanthes-based pastures in the dry season produced more milk, lost less weight, had shorter calving intervals and there was greater calf survival when compared with natural pastures. Leguminous pasture grazing by goats significantly reduced weight losses in the wet season. Both observations were attributed to the greater nutritive value of the forage legume relative to the natural pasture. The nitrogen (N) recycled by legume leys to subsequent crops was assessed in bioassays. Results showed that N supplied by Stylosanthes to subsequent crops varied from 30-80 kg N/ha. Grain yields from areas preceded by the legumes were always higher and in some cases were double those from natural pasture. The superior performance of crops following Stylosanthes was associated with improvement in soil physical and chemical properties caused by the legume. The incorporation of forage legumes into cropping systems shows great potential for the maintenance of sustainable farming systems.